2018
DOI: 10.1021/acssuschemeng.8b04301
|View full text |Cite
|
Sign up to set email alerts
|

Red-Emitting Copper Nanoclusters: From Bulk-Scale Synthesis to Catalytic Reduction

Abstract: A large-scale, easy synthesis of red fluorescent copper nanoclusters (CuNCs) from a cheap source copper acetate, monohydrate has been reported. A proteinaceous amino acid cysteine has been used to stabilize these clusters at room temperature. These nanoclusters have been thoroughly characterized by UV–vis absorption, fluorescence spectroscopy, matrix-assisted laser desorption ionization time-of-flight (MALDI-TOF) spectrometry, transmission electron microscopy (TEM), X-ray powder diffraction analysis, cyclic vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 77 publications
0
43
0
Order By: Relevance
“…However, the authors showed that while using tetrakis(hydroxymethyl)phosphonium chloride (THPC) as a reducing agent, not only the stability of the dihydrolipoic acid (DHLA)-stabilized cluster increases due to additional interaction with copper core, but also the PL can be tuned from red 110 to bright orange emission 111 depending on the applied reaction conditions. Other ligands such as (3mercaptopropyl)trimethoxysilane, 112 D-penicillamine, [113][114][115] cysteine, [116][117][118][119][120][121][122][123] mercaptobenzoic acid, 124,125 peptides (in particular glutathione (GSH)) 17,18,[126][127][128][129][130][131][132][133][134][135][136][137] and small organic molecules [138][139][140][141][142] were successfully applied as capping agents for the synthesis of luminescent clusters in a typical Brust-Schiffrin method ( Fig. 6).…”
Section: Modified Brust-schiffrin Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…However, the authors showed that while using tetrakis(hydroxymethyl)phosphonium chloride (THPC) as a reducing agent, not only the stability of the dihydrolipoic acid (DHLA)-stabilized cluster increases due to additional interaction with copper core, but also the PL can be tuned from red 110 to bright orange emission 111 depending on the applied reaction conditions. Other ligands such as (3mercaptopropyl)trimethoxysilane, 112 D-penicillamine, [113][114][115] cysteine, [116][117][118][119][120][121][122][123] mercaptobenzoic acid, 124,125 peptides (in particular glutathione (GSH)) 17,18,[126][127][128][129][130][131][132][133][134][135][136][137] and small organic molecules [138][139][140][141][142] were successfully applied as capping agents for the synthesis of luminescent clusters in a typical Brust-Schiffrin method ( Fig. 6).…”
Section: Modified Brust-schiffrin Techniquementioning
confidence: 99%
“…157 The corresponding silyl formats were obtained after 48 h in acetonitrile, at 45 °C and 1 atm pressure of CO2. Recently Kingshuk Basu et al 118 have prepared red emitting cys-CuNCs and demonstrated its catalytic activity for the reduction of 4-nitrophenol to 4-aminophenol at room temperature. The catalyst can be recycled without loss in activity.…”
Section: Electrocatalytic Reactionsmentioning
confidence: 99%
“…Finally, we outline current challenges and our perspective on the development of CuNCs.When decreasing the size of nanoparticles so that it approaches the Fermi wavelength of an electron, novel optical, electrical and magnetic properties appear (Deng et al 2018a; Li et al 2016b;Moghadam and Rahaie 2019;Wang et al 2018c). Commonly termed nanoclusters (NCs), these ultra-small nanoparticles, bridging the missing link between atoms and nanocrystals, have attracted considerable attention in both fundamental research and practical applications (Bagheri et al 2017;Basu et al 2019;Sun et al 2019;Wang et al 2016b). Benefiting from the great progress in nanosynthetic chemistry, high-quality Copper NCs (CuNCs) with tailored size and good stability can be easily obtained.…”
mentioning
confidence: 99%
“…[27] Additionally, compared to CuNCs, AgNCs and AuNCs are limited to application due to the high cost of fabrication. [28] Meanwhile, CuNCs can be excited with a maximum absorption wavelength of 340 nm and exhibit an overall fluorescence emission in the range of 570-600 nm, so its stokes shifting is quite favorable for the elimination of interference from background signals of complex biological systems. [29] At present, the CuNCs as a kind of chemical sensor has attracted significant attention for the sensing of nitrite ion, [30] iodine, [31] Hg 2 + , [32] Fe 3 + , [33] Al 3 + and pyridoxal 5'-phosphate, [34] trypsin, [27] H 2 O 2 , [29] glucose, [35] MicroRNAs, [36] actin, [37] heparin, [38] β-galactosidase, [39] methyl mercaptan, [40] glutathione and ascorbic acid.…”
Section: Introductionmentioning
confidence: 99%
“…[45] Later, Basu et al used a simple and stabilizer-free chemical reduction method for the gram-scale synthesis of CuNCs with 15 days stability by cheap metal precursor copper acetate and stabilizing the CuNCs by a thiol containing proteinaceous amino acid cysteine. [28] Cu 2 + induced 3-mercaptopropionic acid functionalized copper nanoclusters (Cu 2 + @MPA-CuNCs, QYs = 4.8 %) was developed by a one-pot reaction as a fluorescent probe for the sulfide ion assay with a LOD of 26.3 nM. [46] Recently, a colorimetric and fluorometric dual-signal sensing platform was successfully exploited for the assay of H 2 O 2 , choline and AChE activity based on the chitosan (CS) modified glutathione-protected copper nanoclusters (CS@GSH-CuNCs); meanwhile, the peroxidase-like activity and stability of CS@GSH-CuNCs were effectively improved com-pared with those of GSH-CuNCs due to the synergistic catalytic enhancement and protection effect provided by CS.…”
Section: Introductionmentioning
confidence: 99%